LARgE survey – III. Environments of ultra-massive passive galaxies at cosmic noon: BCG progenitors growing through mergers. Issue 1 (20th March 2020) - Sawicki, Marcin; Arcila-Osejo, Liz; Golob, Anneya; Moutard, Thibaud; Arnouts, Stéphane; Cheema, Gurpreet Kaur
ABSTRACT: We study the environments of a sample of 61 extremely rare z 1.6 Ultra-Massive Passively Evolving Galaxies (UMPEGs: stellar masses M ⋆ >10 11.5 M⊙ ) which – based on clustering analysis presented in Cheema et al. (2020 ) – appear to be associated with very massive ( M halo ∼ 10 14.1 h −1 M⊙ ) dark matter haloes that are likely to be the progenitors of z 0 massive (Coma- and Virgo-like) galaxy clusters. We find that UMPEGs on average have fewer than one satellite galaxy with mass ratio M_^sat :M_^UMPEG ≥ 1:5 (i.e. M_^sat 10^10.8 M⊙ ) within 0.5 Mpc; the large mass gap that we observe between the typical UMPEG and its most massive satellite implies that the z 1.6 UMPEGs assembled through major mergers. Using observed satellite counts with merger time-scales from the literature, we estimate the growth rate due to mergers with mass ratio of ≥1:4 to be ∼13 per cent Gyr −1 (with a 2 × systematic uncertainty). This relatively low growth rate is unlikely to significantly affect the shape of the massive end of the stellar mass function, whose evolution must instead be driven by the quenching of new cohorts of ultra-massive star-forming galaxies. However, this growth rate is high enough that, if sustained to z 0, the typical z 1.6 M_^UMPEG =10 11.6 M⊙ UMPEG can grow into a M ⋆ ≈10 12 M⊙ brightest cluster galaxy (BCG) of a present-day massive galaxy cluster. Our observations favour a scenario in which our UMPEGs are main-branch progenitors of some of the present-day BCGs that have first assembled through major mergers at high redshifts and grown further through (likely minor) merging at later times.